Preventive effect of anti-VacA egg yolk immunoglobulin (IgY) on Helicobacter pylori-infected mice. Issue 3 (8th January 2018) - Hong, Kyung Sook; Ki, Mi-Ran; Ullah, H.M. Arif; Lee, Eun-Joo; Kim, Yong Deuk; Chung, Myung-Jin; Elfadl, Ahmed K.; Park, Jin-Kyu; Jeong, Kyu-Shik
Highlights: Anti-VacA IgY reduced significantly serum levels of anti- H. pylori antibodies. Anti-VacA IgY decreased eosinophilic infiltration in gastric mucosa of mice. Anti-VacA IgY suppressed immunopositivity in gastric mucosa of mice. Abstract: Background: Helicobacter pylori, a gram-negative bacterium, is the causative agent of gastric disorders and gastric cancer in the human stomach. Vacuolating cytotoxin A (VacA) is among the multi-effect protein toxins released by H. pylori that enables its persistence in the human stomach. Methods: To evaluate the effect of anti-VacA egg yolk immunoglobulin (anti-VacA IgY) on H. pylori infection, a highly specific anti-VacA IgY was produced from egg yolks of hens immunized with a mixture of two purified recombinant VacAs. Female C57BL/6 mice were supplemented anti-VacA IgY daily with drinking water for 2 weeks before and 4 weeks after H. pylori ATCC 43504 inoculation. Anti-VacA IgY recognized both native and denatured structures of VacA by enzyme-linked immunosorbent assay and immunoblotting analyses, respectively. Results: Oral administration of anti-VacA IgYs significantly ( p < .05) reduced the serum levels of anti- H. pylori antibodies compared to those in the H. pylori -infected, untreated group. The reduction in the immune response was accompanied by a significant ( p < .05) decrease in eosinophilic infiltration of the stomach in anti-VacA IgY treated group compared to other groups. Concomitantly, H. pylori –induced histological changes and H. pylori antigen-positivity in gastric tissues were decreased significantly ( p < .05) in anti-VacA IgY treated group similar to the control group. Conclusions: Oral administration of anti-VacA IgY is correlated with a protective effect against H. pylori colonization and induced histological changes in gastric tissues. Our experimental study has proved that it is expected to be a new drug candidate of Hp infection by further study.